1999
DOI: 10.1080/00365519950185607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil fatty acids on plasma lipids and lipoproteins and oxidant-antioxidant imbalance in healthy subjects

Abstract: The purpose of this study was to investigate the effect of eicosapentaenoic and docosahexaenoic acids on plasma lipids and lipoproteins, lipid peroxidation and antioxidant status in healthy humans. A total of 19 healthy volunteers consumed 6 g/day Maxepa fish oil for 3 weeks (1.8 g n-3 fatty acids/day). At baseline and at day 21, we evaluated plasma lipoproteins, plasma and low-density lipoprotein fatty acids, lipid peroxidation markers (malondialdehyde concentration, low-density lipoprotein peroxidation in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Moreover, in two prospective follow-up studies it was reported that DHA intake was inversely related to the risk of AMD [3,16]. Of note is the observation that supplemental DHA increases HDL and HDL subfractions in serum [17,18,19]. Given that the carotenoids transport is made by lipids (HDL) [20,21], DHA supplementation could increase its transport to the retina and subsequently cause a MP ocular density (MPOD) increase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in two prospective follow-up studies it was reported that DHA intake was inversely related to the risk of AMD [3,16]. Of note is the observation that supplemental DHA increases HDL and HDL subfractions in serum [17,18,19]. Given that the carotenoids transport is made by lipids (HDL) [20,21], DHA supplementation could increase its transport to the retina and subsequently cause a MP ocular density (MPOD) increase.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated to be implicated in decreased endothelium-dependent dilating capacity associated with hyperglycemia or diabetes [9]. Another aspect in which oxidative mechanisms could potentially be involved is the generalized increase in transvascular passage of macromolecules [10]described in different types of diabetes in animals [11]and also found in patients [12, 13]even at very early stages of the disease [14]. Indeed, several mechanisms have been proposed to explain this increase in transvascular passage of macromolecules associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%